2017
DOI: 10.24917/25438832.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Skin ectoparasites of domestic animals

Abstract: Zwierzęta towarzyszące ludziom, w tym zwierzęta domowe odgrywają ważną rolę w otaczającym nas środowisku. Jednak większość z nich może być narażona na kontakt z gatunkami pasożytniczych roztoczy i owadów, o dużym znaczeniu medycznym i weterynaryjnym, stanowiących zagrożenie dla zdrowia zarówno zwierząt, jak i ludzi. Do najbardziej rozpowszechnionych ektopasożytów skórnych zwierząt należą: Demodex canis, D. cati, D. criceti, D. aurati, D. caviae, Otodectes cynotis, Sarcoptes scabiei, Cheyletiella yasguri, C. bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This is similar to the research of Karma et al (2015) found 252 D. melopsitacci with 100% prevalence in all body regions. This high infestation of mites is due to a decrease in chicken immunity due to stress, lack of nutrition, and a bad environment (Kocon and Chmura, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to the research of Karma et al (2015) found 252 D. melopsitacci with 100% prevalence in all body regions. This high infestation of mites is due to a decrease in chicken immunity due to stress, lack of nutrition, and a bad environment (Kocon and Chmura, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Literature could not be found on clinical infestation of Sideroferus lunula in Budgerigars kept by owners and sellers in Gujarat or India. However; clear evidence of Sideroferus lunula infestation in Budgerigars has been documented by Schmaschke et al (2001), Benardi et al (2013) and Kocon and Nowak-Chmura (2017). Besides Sideroferus lunula, other feather mites such as Dubininia melopsittaci has been documented by Atyeo and Guad (1987), Schmaschke et al (2001) and Kocon and Nowak-Chmura (2017) in Budgerigars.…”
Section: Discussionmentioning
confidence: 98%
“…in Budgerigars kept by owners and sellers in Gujarat and India could not be accessed during the study period. Besides Heteromenopon spp., active clinical infestation by Neopsittacusgracilis lice has been documented by Kocon and Nowak-Chmura (2017) while clinical infestation by Afrimenoponwaar has been documented by Sychra et al (2007) and Dik et al (2013) in countries other than India.…”
Section: Discussionmentioning
confidence: 99%